Faktor risiko stunting pada anak umur 6-24 bulan di kecamatan Penanggalan kota Subulussalam provinsi Aceh - Lestari, Wanda; Margawati, Ani; Rahfiludin, Zen (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2014)
Background : Aceh is one of the province in Indonesia with high prevalence of stunting that is 39% compared withnational 35,6%. Subulussalam has a highly proportion of stunting.Objective : This study was aimed to analyze the risk factors for stunting among children between 6-24 months old.Methods : The design was case-control study, the subjects were children between 6-24 months with 55 stunted and 55normal. The subjects chosen by consecutive sampling. The risk factors were education levels and employment of parent,family income, suffering from diarrhea and URTI, energy and protein intake, height of the parent, birth weight,exclusive breastfeeding, the time of complementary feeding, parenting style and source of clean water. Data analysisusing the odds ratio with 95% confidence interval and regression analysis.Results : The risk factors for stunting were low income of family (OR=8,5, 95%CI: 2,68-26,89), suffering from diarrhea(OR=5,04, 95%CI: 1,84-13,81) and URTI (OR=5,71, 95%CI: 1,95-16,67), inadequate of energy (OR=3,09, 95%CI:1,02-9,39) and protein intake (OR=5,54, 95%CI: 2,43-12,63), short stature of the parent (OR=11,13, 95%CI: 4,37-28,3), low birth weight (OR=3,26, 95%CI: 1,46-7,31), not exclusively breastfeeding (OR=6,54, 95%CI: 2,84-15,06),giving complementary feeding too early (OR=6,54, 95%CI: 2,84-15,06), and poor parenting style of feeding practices(OR=4,59, 95%CI: 2,05-10,25), child hygiene practices (OR=3,26, 95%CI: 1,46-7,31) and treatment of childrenpractices (OR=2,46, 95%CI: 1,13-5,34). Regression analysis showed that the dominant risk factor for stunting wasshort stature of the parent (OR=13,16, 95%CI: 3,72-46,52).Conclusions : The dominant risk factor for stunting was short stature of the parent.